Analisis Layout Melalui Metode Activity Relationship Chart (ARC) dan Activity Relationship Diagram (ARD) (Studi Kasus: Tandi's Bakery) - Marbun, Yemima; Awangsa, Mhd Nurhadi; Chandra, Queena Yovita; Binokasih, Kaulah Diaz Syahira; Simamora, Riky Rivaldo; Nurlela, Nurlela (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to assess the effectiveness of the existing facility layout at Tandi’s Bakery and to propose a more efficient arrangement using a systematic approach based on the Activity Relationship Chart (ARC), Activity Relationship Worksheet (ARW), Activity Relationship Diagram (ARD), and Total Closeness Rating (TCR). The analysis reveals that the current layout is suboptimal, characterized by inappropriate placement of connecting doors, insufficient proximity between interdependent facilities, and a toilet location that is not aligned with the office area. These issues hinder workflow, increase material handling distances, and reduce overall operational efficiency. By evaluating the interrelationships among activities and determining priority levels of facility proximity, this study proposes an improved layout that includes relocating the toilet, reorganizing connecting doors, and restructuring production spaces according to process linkages. The proposed layout is expected to enhance workflow continuity, improve hygiene conditions, and support greater productivity within Tandi’s Bakery.